Effectiveness of Purple Sweet Potato and Red Bean Cookies on Fasting Blood Glucose Levels in Patients with Type II Diabetes Mellitus - Maqhfiratul Ulfa; Rr Sri Endang Pujiastuti; Mardiyono Mardiyono; Emad Mousay Mohammed Amkhatirah (JURNAL INFO KESEHATAN, 2025)
The worldwide prevalence of diabetes mellitus (DM) continues to climb yearly, with 1.5 million fatalities directly related to DM each year. The number of common instances of DM has been progressively growing during the last several decades. Poor dietary management in people with DM is one of the difficulties that commonly leads to uncontrolled blood glucose levels. Purple sweet potato and red bean cookies are utilized as an alternative treatment for persons with DM because purple sweet potatoes and red beans offer benefits in the form of a low glycemic index and high anthocyanin and fibre content. The goal of this research was to show the efficacy of purple sweet potato and red bean cookies on fasting blood glucose levels in individuals with type II diabetes mellitus. This research approach is a randomized control trial with a pretest-posttest design. Research includes 60 respondents split into 2 groups, utilizing a basic random selection approach. The research was performed for 21 days from 23 September to 13 October 2024 at the Sukamakmur health center region, Aceh Besar. This research employed a pre-test post-test difference test utilizing the Wilcoxon test, and the test across groups using the Mann-Whitney test. The findings of the pre-test average fasting blood sugar levels of intervention group respondents revealed results of 230.07 mg/dL to 152.10 mg/dL post-test (p 0.000), whereas the control group average pretest GDP 226.40 mg/dL to 186.60 mg/dL post-test (p 0.001). This research revealed significant changes in both the intervention and control groups before and after treatment. Statistical findings indicated that purple sweet potato and red bean cookies were more successful in decreasing blood glucose levels than purple sweet potato 104-gram cookies. Purple sweet potato and red bean cookies are excellent to be utilized as nutritious and practical snacks as a support system for persons with DM.